Implementation of data security system in Tabung Haji and SOCSO - Ahmad, Jasmin Ilyani (2003)
This study is revolves in the data security system that was performed in Social Security Concept (SOCSO) and Tabung Haji. Both organizations used router encryption technique where data that will be transferred will be encrypted and decrypted at router. This situation will cause the original data can be tap or modified by unauthorized users during transfer process, before it sent to the router to be encrypted and after decrypted at the next router. This security was developed to avoid the original data that transferred are being modifies before reach at the router. Besides, this system is developed based on the Caesar cipher technique that was improved its security by adding the key from 25 to 255 keys. With this system, the tap or modified problem can be reduced as well as improving the organizations reliability.